Sfera publiczna, sfera prywatna i wolność religijna - Woleński, Jan (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This paper considers the problem of religious freedom in the context of Polish Constittution (1997). One should distinguish religious liberty (right to do something) and religious freedom (independence of religion). Both cases are difficult to be sharply delimited, similarly as interference of religious sphere and out-religious sphere comprising law and morality as basic forms of social control. The rational regulation of the problem of religious liberty and freedom should aim at a proper equilibrium between sacrum and profanum in the democratic system. The author points out that Polish state does not succeed in this respect
Keywords: wolność wyznania